2012
DOI: 10.1103/physrevlett.108.158101
|View full text |Cite
|
Sign up to set email alerts
|

Bistability and Spatiotemporal Irregularity in Neuronal Networks with Nonlinear Synaptic Transmission

Abstract: We present a mean-field theory for spiking networks operating in the balanced excitation-inhibition regime, with synapses displaying short-term plasticity. The theory reveals a novel mechanism for bistability which relies on the nonlinearity of the synaptic interactions. As synaptic nonlinearity is mainly controlled by the spiking rates, the different states are stabilized by dynamically generated changes in the noise level. Thus, in both states, the network operates in the fluctuation-driven regime, producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 21 publications
2
88
0
Order By: Relevance
“…Rather, if we scale Jij1/N, as would be the case for classical balanced networks (van Vreeswijk and Sompolinsky, 1998), then for very large N the solution no longer depends upon the gain L. Finite N or the inclusion of synaptic nonlinearities through short term plasticity (Mongillo et al, 2012) may be necessary to satisfy condition bold𝐂𝟐 with large synapses. Furthermore, the large synaptic weights associated with Jij1/N do not allows us to neglect polysynaptic paths, as is needed for Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…Rather, if we scale Jij1/N, as would be the case for classical balanced networks (van Vreeswijk and Sompolinsky, 1998), then for very large N the solution no longer depends upon the gain L. Finite N or the inclusion of synaptic nonlinearities through short term plasticity (Mongillo et al, 2012) may be necessary to satisfy condition bold𝐂𝟐 with large synapses. Furthermore, the large synaptic weights associated with Jij1/N do not allows us to neglect polysynaptic paths, as is needed for Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…Such activity is typically seen in working memory, and various solutions to this problem have been proposed, which include the uses of slow reverberating synaptic current (Wang, 1999), balanced excitatory and inhibitory synaptic input (Renart et al, 2007; Roudi and Latham, 2007; Mongillo et al, 2012), short-term synaptic depression (Barbieri and Brunel, 2007; Mongillo et al, 2012), and modular network structure (Lundqvist et al, 2010). In this study, we have shown that long-tailed distributions of EPSP amplitudes generate a highly irregular persistent activity in the memory retrieval, as was the case in spontaneous activity (Teramae et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Balanced networks at low rates show a linear input-output relation (38), whereas bistability requires nonlinearities (22,24,27,39). Extensive theoretical work has aimed to reconcile multistability and irregular firing, mainly in the context of persistent activity circuits (40,41). We simplified the problem and, assuming a balanced state during active periods, built a rate network model to investigate the transition dynamics between the two attractors.…”
Section: Discussionmentioning
confidence: 99%